Theory of microcrediting in transitional economies - Kadoić, Nikola (Array, 2009)
Abstract: In the early 1970s, Bangladeshi banker and economist Dr. Muhammad Yunus designed microcrediting – a socially sensitive and rightful system of fighting poverty and high unemployment rates. His Grameen Bank for the poorest of the poor in Bangladesh has so far lifted more than 3.2 million of individuals and their families out of poverty. After initial successes at home, microcredit was put into service for reducing unemployment and alleviating poverty in numerous countries throughout the world. This paper explores specific problems that a typical transitional country (like Croatia), is likely to face, with unemployment – the source of a vast number of related problems in a transitional society – as the focal point. The authors have attempted to incorporate particularities of a transitional economy into the original microcrediting principles.